2015
DOI: 10.2217/ica.14.71
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable scaffolds for the treatment of complex lesions: are we there yet?

Abstract: The introduction of bioresorbable vascular scaffolds (BRS) is changing the landscape of percutaneous coronary revascularization and is considered by many the 4th revolution in interventional cardiology. To date, BRS have shown promising short-and long-term results in the treatment of simple de novo lesions. Even though the feasibility, efficacy and safety of BRS implantation for more complex lesion subsets remain unknown, reports are emerging aiming to identify the role of BRS in everyday practice. In the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Ormiston et al (23) reported on a "snuggling" technique, where only a small portion of SB balloon comes back in MB, and is infl ated at 5 atm, to avoid BVS scaffold fracture. The use of hybrid techniques, where DES is used to treat SB is advised in complicated bifurcations where single provisional stenting with BVS is not enough (22,25). In another case report, Okamura et al (24) describes a patient with an initially peri-proceduraly obstructed SB.…”
Section: Discussionmentioning
confidence: 99%
“…Ormiston et al (23) reported on a "snuggling" technique, where only a small portion of SB balloon comes back in MB, and is infl ated at 5 atm, to avoid BVS scaffold fracture. The use of hybrid techniques, where DES is used to treat SB is advised in complicated bifurcations where single provisional stenting with BVS is not enough (22,25). In another case report, Okamura et al (24) describes a patient with an initially peri-proceduraly obstructed SB.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world BRS registries 22 have demonstrated overall acceptable mid-term outcomes, albeit with some worrying signs of increased stent thrombosis. Ishibashi et al 9 summarized the stent thrombosis experience with BRS in various settings (stable angina, ACS, STEMI).…”
Section: Discussionmentioning
confidence: 99%
“…Definite/probable thrombosis rate in the BVS group was numerically higher at both 30 days (2.1% vs 0.3% [ P =0.059] vs 1.0% [ P =0.324], respectively) and 1 year (2.4% vs 1.4% [ P =0.948] vs 1.7% [ P =0.825], respectively), as compared with the EES or BMS groups. Several smaller registries have demonstrated the feasibility of implantation of BVS in more complex lesions, 75 such as calcified lesions 76 or ISR. 77 Table 2 shows the landmark studies in patients treated with EESs/everolimus-eluting scaffolds.…”
Section: Comparative Efficacy and Safety Of Eessmentioning
confidence: 99%